BADAN KEHORMATAN SEBAGAI ALAT KELENGKAPAN DALAM MENJAGA MARTABAT DAN KEHORMATAN DEWAN PERWAKILAN RAKYAT DAERAH KOTA BATAM - Putra Yustisi Respaty; Ramon Nofrial Erni Yanti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
The Honorary Board of the Regional House of Representatives of Batam City is an internal supervisory institution with an active function, namely supervision in evaluating absenteeism, legal products produced by the DPRD, and the intensity of meetings of council members, and a passive function, namely following up when there are complaints indicating violations by board member. The Honorary Body has the task of carrying out supervision and control over DPRD members, aiming to maintain and uphold the honor and nobility of the people's representative institutions. Factors that affect the role of the Honorary Board of Directors include: the absence of special rules for the recruitment of Honorary Board members, weak DPRD rules and regulations, the absence of procedural guidelines, problems with complaints mechanisms or procedures, complainants lack cooperation, and the nature of solidarity between DPRD members. In dealing with these factors, the Honorary Board seeks to be more active in supervising by observing the behavior of each member of the council, as well as optimizing facilities in the form of supporting facilities and infrastructure.